2011
DOI: 10.1021/jf103908d
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Insecticidal Activities of Novel Monohalovinylated Pyrethroids

Abstract: A series of novel monohalovinylated pyrethroids are designed and synthesized to replace one halo atom with a hydrogen atom on the double bond of dihalopyrethroids. Bioassays indicate that some of the synthesized compounds, such as 3j and 1j, exhibit high insecticidal activities against mosquitoes ( Culex pipiens pallens ), oriental armyworms ( Mythimna separata ), alfalfa aphids ( Aphis medicagini ), and carmine spider mites ( Tetranychus cinnabarinus ). Photolytic results of E-cis-1j suggest that monohaloviny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Bonding of fluorine to usnic acid decreased the concentration required to achieve a stable insecticidal effect. It is well known that the bonding of halogen atoms (including fluorine) to organic insecticides increases both the efficacy and range of target insects . Halogen‐containing pyrethroids affect insect immunity by oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bonding of fluorine to usnic acid decreased the concentration required to achieve a stable insecticidal effect. It is well known that the bonding of halogen atoms (including fluorine) to organic insecticides increases both the efficacy and range of target insects . Halogen‐containing pyrethroids affect insect immunity by oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the bonding of halogen atoms (including fluorine) to organic insecticides increases both the efficacy and range of target insects. 47,48 Halogen-containing pyrethroids affect insect immunity by oxidative stress. 49,50 Fluoride ions act as enzymatic poisons, inhibiting the activity of different enzymes (e.g., alkaline phosphatase, adenosine triphosphatase, phosphorylase), which leads to disturbance of important metabolic processes such as glycolysis and protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Reagents and solvents not listed and not specified were purchased from commercial suppliers. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, since the synthesized compound contains small amount of impurities and the area integral in the 1 H NMR spectrum is substantially less than 0.5, it is difficult to accurately determine the content thereof. Because the synthesized compounds are all novel compounds, and the exact purity of the compound cannot be determined by the HPLC absorption peak, only rough values of the initial purity determined by NMR are given in the following compound data.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
“…The activities of insecticides against fourth-instar mosquito larvae (wrigglers) were tested by the dipping method according to the reported procedure. 11,25 2.6 Resistance level of compounds DCA-O, DCA-01, DCA-03, DCA-04, DCA-08, DCA-11 One of the alternative methods in monitoring resistance is the bottle bioassay adopted by the US CDC, which is a surveillance tool used to detect the change in susceptibility to insecticides in mosquito vector populations.…”
Section: Insectidicides Test For Mosquitomentioning
confidence: 99%
“…Furthermore, as a kind of biomimetic insecticides structurally derived from the natural pyrethrins, pyrethroids such as fenpropathrin, bifenthrin, tefluthrin, and tetramethrin (Figure ) have widely been used in agriculture and have received continuous attention for decades due to their remarkable properties including high activity, broad insecticidal spectrum, and low toxicity to mammals and birds. However, during the use of pyrethroids, some issues such as the generation of resistance and formation of residues in high quantities have always been accompanied. For example, the residual amount of both fenpropathrin and cyfluthrin in tap water after 28 days of application was found to be 5 times that of the organophosphate insecticide Cyanophos; it has also been reported that the long-term application of bifenthrin has brought a negative impact on the pest control in Australian cotton due to the resistance development . Therefore, further structural modifications for this kind of insecticides are still needed.…”
Section: Introductionmentioning
confidence: 99%